Otolith growth chronologies reveal distinct environmental sensitivities between and within shallow- and deep-water snappers - Joseph B. Widdrington; Patrick Reis-Santos; John R. Morrongiello; Jed I. Macdonald; Corey B. Wakefield; Stephen J. Newman; Simon J. Nicol; Bronwyn M. Gillanders (Reviews in Fish Biology and Fisheries, 2025)
Fish growth underpins individual fitness and population-level metrics, with fluctuations linked to environmental variability. Growth chronologies derived from otolith increment analysis are a powerful proxy to understand population responses to environmental change and productivity. Yet, long-term patterns of growth and their environmental drivers are better understood for shallow-water species compared to deep-water inhabitants. Additionally, focus is largely on adults, disregarding the potential influence of juvenile growth which is critical to size- and age-at-maturity. Here, we investigate the long-term growth patterns of two commercially important snapper species separated by depth in northwestern Australia’s coastal shelf waters, the shallow-water Lutjanus sebae (70 year chronology, 1950–2020) and the deep-water Etelis boweni (41 year chronology, 1973–2013). Annually-resolved otolith growth chronologies revealed distinct environmental sensitivities within (juveniles vs adults) and among (shallow- vs deep-water habitats) species. Within species, juveniles and adults responded differently to shared environmental stimuli, highlighting the importance of understanding the impacts of environmental effects and sensitivities for different life-history stages. Across species, L. sebae exhibited highly variable growth tied to local climate signals such as sea surface temperature and rainfall, while E. boweni displayed more stable growth patterns that only responded to interannual and decadal shifts in the environment (e.g. Pacific Decadal Oscillation). Our results highlight potential vulnerabilities of shallow-water species to future environmental perturbations compared to species residing at depth, as they are likely to encounter more extreme climate variability under future oceanic conditions. This study contributes valuable insights into understanding and managing the impacts of future environmental variability on fisheries sustainability, emphasising the need for continued research across species and habitats.

How accurate is your average? Considering error when counting sea lice on open-pen salmon farms - Alexes Mes; Jed Stephens; Matthew Palmer; Rachel Mulrenan; Corin Smith (Aquaculture, 2024)

Dynamically simulating spruce budworm in eastern Canada and its interactions with wildfire - Hiromitsu Sato; Emeline Chaste; Martin P. Girardin; Jed O. Kaplan; Christelle Hély; Jean-Noël Candau; Stephen J. Mayor (Ecological Modelling, 2023)

Spatial and temporal variations in interspecific interaction: impact of a recreational landscape - Solène Marion; Urška Demšar; Althea L. Davies; Philip A. Stephens; R. Justin Irvine; Jed A. Long (European Journal of Wildlife Research, 2022)
Anthropogenic activities, such as outdoor recreation, have the potential to change complex interactions between wildlife and livestock, with further consequences for the management of both animals, the environment, and disease transmission. We present the interaction amongst wildlife, livestock, and outdoor recreationists as a three-way interaction. Little is known about how recreational activities alter the interaction between herbivores in areas extensively used for recreational purposes. We investigate how hiking activity affects spatio-temporal co-occurrence between domestic sheep ( Ovis aries ) and red deer ( Cervus elaphus ). We used camera traps to capture the spatio-temporal distribution of red deer and sheep and used the distance from the hiking path as a proxy of hiking activity. We used generalized linear models to investigate the spatial distribution of sheep and deer. We analysed the activity patterns of sheep and deer and then calculated their coefficients of temporal overlap for each camera trap location. We compared these coefficients in relation to the distance from the hiking path. Finally, we used a generalized linear mixed-model to investigate which factors influence the spatio-temporal succession between deer and sheep. We do not find that sheep and red deer spatially avoid each other. The coefficient of temporal overlap varied with distance from the hiking trail, with stronger temporal co-occurrence at greater distances from the hiking trail. Red deer were more likely to be detected further from the path during the day, which increased the temporal overlap with sheep in these areas. This suggests that hiking pressure influences spatio-temporal interactions between sheep and deer, leading to greater temporal overlap in areas further from the hiking path due to red deer spatial avoidance of hikers. This impact of recreationists on the wildlife and livestock interaction can have consequences for the animals’ welfare, the vegetation they graze, their management, and disease transmission.

Culling recolonizing mesopredators increases livestock losses: Evidence from the South African Karoo - Nicoli Nattrass; Beatrice Conradie; Jed Stephens; Marine Drouilly (Ambio, 2020)

Erratum to: The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; H. John B. Birks; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; et al. (Vegetation History and Archaeobotany, 2013)

The European Modern Pollen Database (EMPD) project - Basil A. S. Davis; Marco Zanon; Pamella Collins; Achille Mauri; Johan Bakker; Doris Barboni; Alexandra Barthelmes; Celia Beaudouin; Anne E. Bjune; Elissaveta Bozilova; Richard H. W. Bradshaw; Barbara A. Brayshay; et al. (Vegetation History and Archaeobotany, 2013)

Beta diversity of marine bacteria depends on temporal scale - Stephen M. Hatosy; Jennifer B. H. Martiny; Rohan Sachdeva; Joshua Steele; Jed A. Fuhrman; Adam C. Martiny (Ecology, 2013)
Factors controlling the spatial distribution of bacterial diversity have been intensely studied, whereas less is known about temporal changes. To address this, we tested whether the mechanisms that underlie bacterial temporal β‐diversity vary across different scales in three marine microbial communities. While seasonal turnover was detected, at least 73% of the community variation occurred at intra‐seasonal temporal scales, suggesting that episodic events are important in structuring marine microbial communities. In addition, turnover at different temporal scales appeared to be driven by different factors. Intra‐seasonal turnover was significantly correlated to environmental variables such as phosphate and silicate concentrations, while seasonal and interannual turnover were related to nitrate concentration and temporal distance. We observed a strong link between the magnitude of environmental variation and bacterial β‐diversity in different communities. Analogous to spatial biogeography, we found different rates of community changes across temporal scales.